Tinjauan Yuridis Saksi Instrumentair Dalam Akta Notariil - Marham Kertawadi; Lalu Husni; Muhaimin - (Fakultas Hukum Universitas Mataram, 2017)
This study aims to analyze the witness of instrumentair which is a matter related to the Notary and its aktanya products, which should have been set forth in the UUJN regarding matters relating to the witness, although instrumentair witness action in the inauguration of notarial deed is included in the field of notarization , But the Notary's Office Law does not provide special arrangements concerning instrumentair witnesses primarily related to the legal protection and legal liability of instrumentair witnesses, in the Notary Law only regulating legal protection and legal responsibility of Notaries only. In the above explanation the authors found the existence of a void of norms in the Law of Notary Public that is related to the protection of law and responsibility of Notary public as instrument witness in notariil deed so that the confidentiality of a deed is maintained from unauthorized parties to the deed including Police In the inspection process. This research uses normative research method by using approach of legislation and concept approach. The result of the research in this thesis is that the instrumentair witness is not responsible for the contents of the deed in its signature as witness, the instrumentair witness is only personally responsible based on the Act, but only on the formalities which are run in the process of making or The inauguration of the deed and the protection of instrumentair witnesses in the examination by the Police in a juridical manner the instrumentair witness received the protection as a witness in general which is regulated in the Witness and Victim Protection Act set out in Law No.13 of 2006.